Seawater carbonate chemistry and oxygen, proton flux and calcification of two Hawaiian coral species - David A Armstrong; Conall G McNicholl; Keisha D Bahr (PANGAEA, 2026)
This study examines two Hawaiian coral species—Montipora capitata and Pocillopora acuta to elevated pCO2 simulating OA. Utilizing pH and O2 microsensors under controlled light and dark conditions, this work characterized interspecific concentration boundary layer (CBL) traits and quantified material fluxes under ambient and elevated pCO2. This dataset is included in the OA-ICC data compilation maintained in the framework of the IAEA Ocean Acidification International Coordination Centre (see https://oa-icc.ipsl.fr). Original data were downloaded from Github (see Source) by the OA-ICC data curator. In order to allow full comparability with other ocean acidification data sets, the R package seacarb (Gattuso et al, 2024) was used to compute a complete and consistent set of carbonate system variables, as described by Nisumaa et al. (2010). In this dataset the original values were archived in addition with the recalculated parameters (see related PI). The date of carbonate chemistry calculation by seacarb is 2026-01-21.